New Testament Studies in Religion Past and Present - DeMaris, Richard (Bulletin for the Study of Religion, 2015)
This short review cannot do justice to more than a handful of articles on, or related to, the New Testament. So I will offer some comments about Religion Past and Present (Betz et al. 2007–2013) as a whole and observe how the conceptualization and agenda of the encyclopedia have manifested themselves in the details—at the level of a few specific articles.